MICROENCAPSULATION OPTIMIZATION OF PROPOLIS ETHANOLIC EXTRACT FROM TETRAGONULA SPP USING RESPONSE SURFACE METHODOLOGY - PRATAMI, DIAH KARTIKA; MUN’IM, ABDUL; HERMANSYAH, HERI; GOZAN, MISRI; SAHLAN, MUHAMAD (International Journal of Applied Pharmaceutics, 2020)
Objective: This research aimed to encapsulate the propolis through spray drying to overcome problematic handling properties of propolis and to optimize the microencapsulation by using response surface methodology (RSM). Methods: The propolis ethanolic extract (PEE) was microencapsulated by spray drying with maltodextrin and gum arabic. RSM was applied for the optimization of microencapsulation efficiency, yield, moisture content, solubility in water, total phenolic content (TPC), and antioxidant activity of spray-dried propolis (SDP) microcapsules. Results: The highest process efficiency reached a microencapsulation yield of 75.35%. The highest solubility of SDP in water was 91.47%, with a moisture content of 0.96%. SDP exhibiting the highest TPC of 307.325 mg GAE/g, with a microencapsulation efficiency of 81.48%. Ferric reducing antioxidant power analysis showed its highest antioxidant activity with a low EC50 19.12 ug/ml with DPPH analysis, and a high reducing power capacity of 314.64 mg GAE/g. Conclusion: Microencapsulation optimization of propolis ethanolic extract from Tetragonula spp. using RSM indicated that SDP with 1:2 ratios of the microwall to core (propolis), inlet temperature at 115 °C, and flow rate 20% represented the optimum conditions. Microencapsulation has successes improved physical appearance and the solubility index and protected and enhanced bioactive compounds and antioxidant properties of propolis in optimum condition by using spray drying.